PENGEMBANGAN MODUL PADA MATA PELAJARAN PRODUKKREATIF DAN KEWIRAUSAHAAN UNTUK SISWA KOMPETENSIKEAHLIAN TEKNIK KENDARAAN RINGAN OTOMOTIF SMK N 2PENGASIH - Nanang Setiawan (Universitas Negeri Yogyakarta, 2020)
AbstractThis research aims to compile learning module for Creative Products and Entrepreneurship which is in accordance with XI class of Automotive Light Vehicle Engineering Skills Competencies, and to find out the feasibility of the Creative Products and Entrepreneurship module in SMK N 2 Pengasih. This method used 4D development research model from Thiagarajan. The subjects were material experts, media experts, and 36 TKRO XI students in SMK N 2 Pengasih. Collecting data using a questionnaire with Likert scale and analyzed to obtain feasibility results. The validity used content with expert opinion (expert judgment). Data analysis used quantitative descriptive analysis. The result: compilation of learning modules for Creative Products and Entrepreneurship for learning activities in SMK N 2 Pengasih in XI Class of Automotive Light Vehicle Engineering Skills Competency. Feasibility according to material experts obtains a percentage score of 88.6% which is included in